2021
DOI: 10.1088/1742-6596/1769/1/012017
|View full text |Cite
|
Sign up to set email alerts
|

Convolution Neural Network Application in the Simultaneous Detection of Gender and Variety of Silkworm (Bombyx mori) Cocoons

Abstract: Convolution neural network (CNN) has been widely studied in the field of computer vision with good results, and a lot of research is still needed to show its application effect in the near-infrared spectroscopy with 1-D input data and small sample set. In this paper, the near-infrared diffuse transmission spectra of 2386 silkworm (Bombyx mori) cocoons from the 4th day of cocooning to the 13th day before turning into moths were collected. After the mean center preprocessing, CNN, SVM and LDA were used to model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The prototype described in this paper was conceived by the authors to substitute for selection at the farmers’ site, which is very time-demanding and therefore critical in increasing production costs. The idea is that cocoon producers can transport their cocoons to the drying plant, where they can convey and desiccate their cocoons separately from other farmers (thanks to the traceability process established in the Serinnovation project) and according to the different quality classes (grades); the final aim is to calculate an adequate remuneration for each farmer, according to the accuracy of the work individually performed and, therefore, the quality of their eventual output [ 13 ], and also to transfer an already almost completely sorted product to the reeling plant to diminish selection work on cocoons to be reeled at the industrial place. The prototype was based on a patented idea [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prototype described in this paper was conceived by the authors to substitute for selection at the farmers’ site, which is very time-demanding and therefore critical in increasing production costs. The idea is that cocoon producers can transport their cocoons to the drying plant, where they can convey and desiccate their cocoons separately from other farmers (thanks to the traceability process established in the Serinnovation project) and according to the different quality classes (grades); the final aim is to calculate an adequate remuneration for each farmer, according to the accuracy of the work individually performed and, therefore, the quality of their eventual output [ 13 ], and also to transfer an already almost completely sorted product to the reeling plant to diminish selection work on cocoons to be reeled at the industrial place. The prototype was based on a patented idea [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A further study identified the sex of silkworm pupae using radial-based neural networks (RBF-NNs), through which an accuracy rate of more than 98% was achieved [ 13 ].…”
Section: Introductionmentioning
confidence: 99%